1998
DOI: 10.1021/ie980403w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Control of a Batch Polymerization Reactor:  Experimental Study

Abstract: A parameter estimation procedure was developed to fit a kinetic model with the experimental data obtained from methyl methacrylate (MMA) solution polymerization in a 10 L batch reactor. For molecular weight control, we applied the modified two-step method in calculating the optimal temperature trajectory on the basis of the identified kinetic model. Application of a conventional proportional-integral (PI) controller to track the temperature trajectory proved to be acceptable in a conventional batch reactor wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 11 publications
0
15
0
3
Order By: Relevance
“…Ellis et al (1994) obtained good experimental results for the estimation of the molecular weight distribution (MWD) in a batch polymerization reactor by using online densitometer and online size exclusion chromatograph (SEC), and then controlled the polymer quality with a PID controller. The application of online measurement devices has also been reported in other research works (Echevarria et al, 1998;Chylla et al, 1997;Chang and Liao, 1999) and an excellent review on the online measurement techniques has been presented by Ohshima and Tanigaki (2000).…”
Section: Introductionmentioning
confidence: 95%
“…Ellis et al (1994) obtained good experimental results for the estimation of the molecular weight distribution (MWD) in a batch polymerization reactor by using online densitometer and online size exclusion chromatograph (SEC), and then controlled the polymer quality with a PID controller. The application of online measurement devices has also been reported in other research works (Echevarria et al, 1998;Chylla et al, 1997;Chang and Liao, 1999) and an excellent review on the online measurement techniques has been presented by Ohshima and Tanigaki (2000).…”
Section: Introductionmentioning
confidence: 95%
“…The measurement noise for X, HI, andM n was assumed to be σ X = 0.01, σ HI = 0.1, and σM n = 5000 kg/kmol, respectively, according to our previous experimental work [22]. The eight batches (U 8 ( 8 3 )) with repeated measurements at the sampling time (symbols shown in Fig.…”
Section: Hnnrf Model Development For the Batch Polymerization Reactormentioning
confidence: 99%
“…For example, the melt index is often considered as the product quality in polymerization processes (Mat Noor et al, 2010;Liu and Gao, 2015;Lou et al, 2012;Zhang et al, 2006). However, recent studies have shown the fact that the economic gain can be further improved by shaping the distributed output since it can significantly influence the product quality and process efficiency (Alhamad et al, 2005;Braatz and Hasebe, 2002;Chang and Liao, 1999;Nagy, 1999;Nagy and Braatz, 2012;Pigeon et al, 2011;Wang, 2000). Generally, such chemical processes are non-Gaussian and may also show strong nonlinearities (Wang, 2000(Wang, , 2002Zeaiter et al, 2006).…”
Section: Introductionmentioning
confidence: 99%